Microglia regulate cortical remyelination via TNFR1-dependent phenotypic polarization - Athena Boutou; Ilias Roufagalas; Katerina Politopoulou; Spyros Tastsoglou; Maya Abouzeid; Giorgos Skoufos; Laia Verdu de Juan; Jeong Hun Ko; Vasiliki Kyrargyri; Artemis G. Hatzigeorgiou; Christopher J. Barnum; Raymond J. Tesi; et al. (Cell Reports)
Summary: Microglia are strongly implicated in demyelinating neurodegenerative diseases with increasing evidence for roles in protection and healing, but the mechanisms that control CNS remyelination are poorly understood. Here, we show that microglia-specific deletion of tumor necrosis factor receptor 1 (TNFR1) and pharmacological inhibition of soluble TNF (solTNF) or downstream interleukin-1 receptor (IL-1R) allow maturation of highly activated disease-associated microglia with increased size and myelin phagocytosis capacity that accelerate cortical remyelination and motor recovery. Single-cell transcriptomic analysis of cortex at disease onset reveals that solTNF inhibition enhances reparative IL-10-responsive while preventing damaging IL-1-related signatures of disease-associated microglia. Longitudinal brain transcriptome analysis through disease reveals earlier recovery upon therapeutic loss of microglia TNFR1. The functional relevance of microglia inflammatory polarization pathways for disease is validated in vivo. Furthermore, disease-state microglia producing downstream IL-1/IL-18/caspase-11 targets are identified in human demyelinating lesions. Overall, redirecting disease microglia polarization by targeting cytokines is a potential approach for improving CNS repair in demyelinating disorders.